Work loss in patients with rheumatoid arthritis treated with abatacept, rituximab, tocilizumab or TNF inhibitors: a nationwide direct drug-to-drug comparison - Ulf Lindström; Johan Askling; Katerina Chatzidionysiou; Lotta Ljung; Lars Klareskog; Martin Neovius; Nils Feltelius; Eva Baecklund; Christopher Sjöwall; Helena Forsblad-d’Elia; Carl Turesson; Elisabet Lindqvist; et al. (RMD Open)
Objective To compare work loss after starting tumour necrosis factor inhibitors (TNFi), rituximab, abatacept or tocilizumab in patients with rheumatoid arthritis (RA).Methods We used data from the Swedish Rheumatology Quality Register to identify patients aged 19-62 years who were treated with TNFi (n=15 093), rituximab (n=2123), abatacept (n=1877) or tocilizumab (n=1720) between 2007 and 2020. Data on work loss (0–365 days per year) from sick leave and disability pension were retrieved from linkage to the Social Insurance Agency. Patients in the different treatment arms were balanced regarding baseline covariates using inverse probability weighting (IPTW).Results Work loss increased for patients with RA until drug treatment initiation, reached a peak in the month after treatment initiation and then levelled off. Following IPTW, at 3 years before starting the treatment, there were no statistically significant differences in the mean annual adjusted work loss days between rituximab, abatacept or tocilizumab vs TNFi (mean difference vs TNFi: rituximab 1.1 days, 95% CI −4.5 to 6.7; abatacept 3.3, 95% CI −2.6 to 9.2; tocilizumab 1.2, 95% CI −4.9 to 7.3). At 3 years after starting the treatment (latest January 2021), there were also no statistically significant differences in the mean annual adjusted work loss days (mean difference: rituximab −4.8 days, 95% CI −11.3 to 1.7; abatacept 5.3, 95% CI −1.8 to 12.3; tocilizumab −0.6, 95% CI −7.7 to 6.5).Conclusions Taking channelling into account, patients with RA treated with TNFi, rituximab, abatacept or tocilizumab had similar trajectories of work loss from sick leave and disability pension until treatment initiation, and similar trend breaks and plateau 3 years thereafter.